Justification of terrorism according to World Values Survey (2017-2020) - Pilar Rodríguez Martínez; Antonio Jesús Segura Sánchez; Carmelo Jesús Aguilera Galindo (Research in Globalization, 2022)
In this article we present the factors (pull, push and personal) that allow people to justify terrorism. We build a model that allows us to predict on a global scale, which factors best discriminate between the people who justify - or do not justify - terrorism. Based on data from the seventh wave of the World Values Survey (2017-2020) we compare those who do not justify terrorism with those who justify terrorism (23.7% of those interviewed, N = 69578). The importance of attitudes about democracy turns out to be the variable that predicts cognitive radicalization best.
Keywords: 330; Justification of terrorism; Personal factors; Pull factors; Push factors; World Values Survey